Studi Komputasi Energetika dan Mekanisme Reaksi Degradasi Pestisida Oxamyl di Lingkungan - BADRA SANDITYA RATTYANANDA (Gunung Djati Conference Series, 2022)
The one of main problems in the agriculture field was the presence of pests that can cause crop failure. Pesticide was a chemical substance to accomplish the problem of attack from pests, one type that good enough was the pesticide formulation from oxamyl. Behind its efficacy to eradicate pests, oxamyl was banned in several countries due to environmental pollution issues. Therefore, it was necessary to do research that oxamyl can be degraded spontaneously in the environment. The research was conducted using ORCA 5.0.3 software to calculate the optimal structure using the PBE DFT functional and the 6-31G basis set. The structure that has been optimized with the implicit solvent water SMD method was continued with numerical frequency calculations because the inclusion of the SMD method can only be calculated numerically. Oxamyl degradation reaction occurs simultaneously by hydrolysis and reduction. Degradation with hydrolysis mechanism was endothermic and non-spontaneous at low temperatures, this degradation can be spontaneous when the temperature was increased to 94.4 °C or assisted by the presence of biocatalysts in the form of bacteria from the genus Pseudomonas to reduce activation energy. Degradation by reduction mechanism resulted in the values of G < 0, H < 0 and S > 0 which from these values can be predicted that the reaction will be exothermic and spontaneous at all temperatures. Furthermore, it was necessary to search for the transition state to determine the amount of activation energy of the degradation process. For research in the field, it was necessary to directly add a biocatalyst to optimize the degradation process because the reaction is not spontaneous and requires heat.